ANALISIS PENERAPAN PRINSIP SYARIAH DAN PERKEMBANGAN REKSADANA SYARIAH DI INDONESIA - Windy Puspita; Winda Irmayani Sijabat; Kiki Andrea Putri Hasibuan; Muhammad Ikhsan Harahap (EKSYA : Jurnal Ekonomi Syariah, 2023)
This study aims to further explain how the application of sharia principles in sharia mutual funds and their development. This research uses a qualitative method with content analysis, namely research that is carried out in depth on the object under study and uses secondary data or literature/library studies as a technique in research to obtain research results. This research is also analytical descriptive in nature, namely research that provides a clear and detailed description of the object being studied. The results of the research are based on the mechanism, Islamic mutual funds are managed according to Islamic principles, managed by investment managers, are transparent in terms of investment diversification and are guaranteed and supervised by related institutions (OJK) so that it can be concluded that Islamic mutual funds have implemented Islamic principles in their management mechanisms. However, the development of sharia mutual funds continues to experience ups and downs. From 2018 to 2021, the number of sharia mutual funds has increased. However, the Net Asset Value (NAV) of sharia mutual funds in 2018-2022 has experienced a drastic decline. Sharia mutual funds throughout 2022 will continue to experience a periodic decline both in terms of the number of Islamic mutual funds and in terms of Net Asset Value (NAV). When compared between Islamic mutual funds and conventional mutual funds, Islamic mutual funds are still far behind conventional mutual funds. Conventional mutual funds are far superior to Islamic mutual funds. At the end of 2022, the number of sharia mutual funds is only 274, while the number of conventional mutual funds is 1,846. The Net Asset Value (NAV) of sharia mutual funds is 40,605.11 (in billions of rupiah) while that of conventional mutual funds is 464,257.31 (in billions of rupiah).